Tax Rates with Corruption: Labour-market Effects. Empirical Cross-country Comparisons on OECD Countries - Mária Lackó (Hungarian Academy of Sciences, Institute of Economics, 2006)
The paper investigates how tax rates, corruption and institutional aspects of the labour market influence the size of the segments of the labour market such as unemployment, employment, self-employment and activity in the hidden economy. The novelty of our approach is the theoretical justification of the interaction between the perception of taxes and of corruption, as well as the establishment of a new concept and variable, the subjective tax rate. Alternative regression calculations are carried out on data for OECD countries for the period 1995 to 2000. The tests confirm the validity of the new variable and the results imply the need for a more sophisticated policy approach for influencing labour market outcomes.
Keywords: D73; E26; J2; H26; 330; Taxation; corruption; labour market; hidden economy; Korruption; Schattenwirtschaft; Steuer; Steuertarif; Arbeitsmarkt; Vergleich; Schätzung; OECD-Staaten